2014
DOI: 10.1039/c4ra09886b
|View full text |Cite
|
Sign up to set email alerts
|

Carborane polyimides, synthesis and characterization

Abstract: Here we report the syntheses of polyimides with meta-carborane cages embedded in the polymer chain and their characterizations. Aromatic carborane diamines were prepared by a Sonogashira reaction in the first place; reaction of the obtained diamines with commercially available dianhydride led to the formation of carborane polyimides with high molecular weight. Thermogravimetric analysis (TGA) of the samples showed that they have excellent thermal stability, with 5 wt% decomposition temperatures (T d5% ) higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The bulky cages reduce chain‐to‐chain charge transfer interactions and disrupt regular chain packing, while another reason is the electron‐withdrawing property of the cages which reduces inter‐ and intramolecular interaction and results in less dense chain packing. Thus the segments of the chain can move at relatively low temperatures . TGA of these samples was performed in both nitrogen and dry air.…”
Section: Resultsmentioning
confidence: 99%
“…The bulky cages reduce chain‐to‐chain charge transfer interactions and disrupt regular chain packing, while another reason is the electron‐withdrawing property of the cages which reduces inter‐ and intramolecular interaction and results in less dense chain packing. Thus the segments of the chain can move at relatively low temperatures . TGA of these samples was performed in both nitrogen and dry air.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers with carboranes as building blocks, such as polyurethanes, polythiophenyls, polysiloxanes, and polyimides, are getting some attention due to their good solubility, thermal and thermo‐oxidative stability, and high T g . For example, Huang et al.…”
Section: Methodsmentioning
confidence: 99%
“…
thermal stability by introducing organic heterocyclic groups into polymers' chains. [7,[16][17][18] Polymers with carboranes as building blocks, such as polyurethanes, [19] polythiophenyls, [20] polysiloxanes, [21,22] and polyimides, [23][24][25] are getting some attention due to their good solubility, thermal and thermo-oxidative stability, and high T g . For example, Huang et al reported that an m-carborane-containing polybenzoxazine had outstanding thermooxidative stability and high T g .
…”
mentioning
confidence: 99%
“…Nuclear shielding composites are important materials used for blocking g rays and neutron radiation to ensure safety of personnel and machines. [1][2][3][4][5] Lead-boron polyethylene (PBPE) is widely used for nuclear shielding. The resins have good moderating effect on fast neutrons, while boron atoms can absorb thermal neutrons effectively and Pb atoms have effective shielding effect on g rays.…”
Section: Introductionmentioning
confidence: 99%